The Effects of a Gentle Yoga Program on Sleep, Mood, and Blood Pressure in Older Women with Restless Legs Syndrome (RLS): A Preliminary Randomized Controlled Trial. (28th February 2012) - Innes, Kim E.; Selfe, Terry Kit
Abstract : Objective . To examine the effects of yoga versus an educational film program on sleep, mood, perceived stress, and sympathetic activation in older women with RLS. Methods . Participants were drawn from a larger trial regarding the effects of yoga on cardiovascular disease risk profiles in overweight, sedentary postmenopausal women. Seventy-five women were randomized to receive either an 8-week yoga (n = 38 ) or educational film (n = 37 ) program. All 75 participants completed an RLS screening questionnaire. The 20 women who met all four diagnostic criteria for RLS (n = 10 yoga, 10 film group) comprised the population for this nested study. Main outcomes assessed pre- and post-treatment included: sleep (Pittsburgh Sleep Quality Index), stress (Perceived Stress Scale), mood (Profile of Mood States, State-Trait Anxiety Inventory), blood pressure, and heart rate. Results . The yoga group demonstrated significantly greater improvements than controls in multiple domains of sleep quality and mood, and significantly greater reductions in insomnia prevalence, anxiety, perceived stress, and blood pressure (all P 's≤ 0.05 ). Adjusted intergroup effect sizes for psychosocial variables were large, ranging from 1.9 for state anxiety to 2.6 for sleep quality. Conclusions . These preliminary findings suggest yoga may offer an effective intervention for improving sleep, mood, perceived stress, and blood pressure in older women with RLS.